Keterampilan Kader Posyandu dalam Penimbangan Balita di Wilayah Kerja Puskesmas Dlingo I Kabupaten Bantul, Propinsi D.I Yogyakarta - Harfi Gatra Wicaksono; Herawati Herawati; Th Ninuk Sri Hartini (JURNAL NUTRISIA, 2016)
Background: Integrated service posts (posyandu) is one activities Improvement of nutrition and family. Posyandu is held from, by and for community. one of community health volunteers are skilled to weigh children under 5 years old using hanging scales. The steps of weighing must be done correctly. Weighing steps have been done incorrectly, there are any interpretation of measurement values error. Objective: Our research aimed to assess the liveliness and weighing skill of community health volunteers. Method: A cross-sectional survey was conducted.The study was carried out in 3 villages that consisted 29 integrated service posts in the area of Community health Centre Dlingo I on Mei-Juni 2015. A total of 30 community health volunteers who have duty at weighing section. The weighing skill of community health volunteers were observed 5 times. Age, education, occupation, work period, community health volunteers’ liveliness, training were the independent variables. Logistic regression was used to analyse the hypothese. Result: Our findings demonstrated 80% of community health volunteers categories as active. Meanwhile, as many as 73,3% of community health volunteers categoriesed as skilfull community health volunteers. Weighing skill significantly associated with age ((p=0,000), liveliness (p = 0,027), trainning (p = 0,007). The incorrectly steps were step five and nine. Conclusion: age of CHV is influenced the weighing skill. The study recommends considering age while recruiting CHV through training Keywords : sociodemographic characteristics, weighing skill, community health volunteer, Yogyakarta